FINITE ELEMENT ANALYSIS OF CONCRETE GRAVITY DAM ON STRATIFIED FOUNDATIONS - Sufitriasa, I. B.; Angreni, Ida Ayu Ari; Kusumaningrum, Jennie (Jurnal Ilmiah Desain & Konstruksi, 2009)
Concrete Gravity Dam is a solid concrete structure with its cross-section approximatelytriangular in shape, so proportioned that the external forces exerted on it are resisted byits own weight. The pattern of stress distribution and deformations in the dam foundationsystem are of great concern for safety and economy case of a high gravity dam foundedon stratified weak rock. Any variation in foundation properties would largely affect thesafe design of dam. The objectives of the present study are to analyze stresses anddeformations in dam foundation system due to applied loads. Stresses and deformations inthe dam foundation section under different conditions have been worked out by using 2-Dimensional Finite Element Method.